Channel innovations for inertial microfluidics. Issue 19 (10th September 2020) - Tang, Wenlai; Zhu, Shu; Jiang, Di; Zhu, Liya; Yang, Jiquan; Xiang, Nan
Abstract : A review discussing the channel innovations for inertial microfluidics. Abstract : Inertial microfluidics has gained significant attention since first being proposed in 2007 owing to the advantages of simplicity, high throughput, precise manipulation, and freedom from an external field. Superior performance in particle focusing, filtering, concentrating, and separating has been demonstrated. As a passive technology, inertial microfluidics technology relies on the unconventional use of fluid inertia in an intermediate Reynolds number range to induce inertial migration and secondary flow, which depend directly on the channel structure, leading to particle migration to the lateral equilibrium position or trapping in a specific cavity. With the advances in micromachining technology, many channel structures have been designed and fabricated in the past decade to explore the fundamentals and applications of inertial microfluidics. However, the channel innovations for inertial microfluidics have not been discussed comprehensively. In this review, the inertial particle manipulations and underlying physics in conventional channels, including straight, spiral, sinusoidal, and expansion–contraction channels, are briefly described. Then, recent innovations in channel structure for inertial microfluidics, especially channel pattern modification and unconventional cross-sectional shape, are reviewed. Finally, the prospects for future channel innovations in inertial microfluidic chips are also discussed. The purpose of this review is to provide guidance for the continued study of innovative channel designs to improve further the accuracy and throughput of inertial microfluidics.